Outcomes of Oxidative Stress in Spontaneous Miscarriage. A Cross-Sectional Clinical Prospective Study - Aniqa Shahid, Fakharunissa, Qamarunissa Muhabat, Zainab Maqsood, (Pakistan Journal of Medical & Health Sciences, 2022)
Aims and Objectives: The aims and objectives of current study were to investigate biological role of enzymatic antioxidants against reactive oxygen species in normal and recent spontaneous miscarriage pregnant women. Results: In control group mean standard deviation (mean ±SD), of blood serum levels regarding age, number of spontaneous miscarriages, hemoglobin, random glucose levels, catalase, superoxide dismutase, glutathione peroxidase were (24.8±23.7, 0.00±0.01, 15.4± 2.41, 135.95±3.12, 106.97 ± 13.94, 12.96±1.71, 12.50 ± 6.5) whereas in study group these biomarkers showed a remark able significant (P<0.005) changes such as (25.1±13.7, 2.10±10.01, 13.14± 12.11,145.65±7.10, 98.89 ± 12.84, 10.06±0.11, 7.20 ± 1.0) respectively. Conclusion: The results of this study claimed that in study group the concentration of reactive oxygen species were higher than the enzymatic antioxidants which is a prediction of spontaneous miscarriages in pregnant women.